Manajemen Berbasis Sekolah (MBS): Suatu Paradigma Menuju Madrasah Mandiri (Studi Kasus MA Al-Qodiri Jember Tahun 2007/2008): School-Based Management (SBM): A Paradigm Toward an Independent Madrasah (A Case Study of Madrasah Aliyah Al-Qodiri Jember in the Academic Year 2007/2008) - Ali Saifullah (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2008)
Entering the 21st century, madrasahs in Indonesia face significant managerial weaknesses that hinder their institutional independence. School-Based Management (SBM) has emerged as a strategic paradigm for transforming madrasahs toward independence. This study aims to analyze the readiness of Madrasah Aliyah Al-Qodiri Jember in implementing SBM across leadership, curriculum, human resources, and student management aspects. Using a qualitative case study design, data were collected through in-depth interviews, observation, and documentation, then analyzed taxonomically and componentially. The findings reveal that leadership and curriculum aspects are not yet ready to be promoted as an independent madrasah due to the lack of professional management and curriculum experts. The human resources aspect is also unprepared due to the non-linear educational backgrounds of administrative staff. Conversely, the student management aspect has demonstrated readiness, evidenced by students' successful admission to prominent universities such as UNAIR, UGM, ITB, and UIN. This study recommends full implementation of SBM, linearization of educators' academic backgrounds, and the provision of technical guidelines from the Ministry of Religious Affairs to support independent madrasahs. Memasuki abad XXI, madrasah di Indonesia menghadapi berbagai kelemahan manajerial yang menghambat kemandirian lembaga. Manajemen Berbasis Sekolah (MBS) muncul sebagai paradigma strategis untuk mentransformasi madrasah menuju kemandirian. Penelitian ini bertujuan menganalisis kesiapan Madrasah Aliyah Al-Qodiri Jember dalam mengimplementasikan MBS pada aspek kepemimpinan, kurikulum, ketenagaan, dan kesiswaan. Dengan pendekatan kualitatif rancangan studi kasus, data dikumpulkan melalui wawancara mendalam, observasi, dan dokumentasi, lalu dianalisis secara taksonomik dan komponensial. Hasil penelitian menunjukkan bahwa aspek kepemimpinan dan kurikulum madrasah belum siap dipromosikan menjadi madrasah mandiri karena belum diterapkannya manajemen profesional serta belum adanya tenaga ahli kurikulum. Aspek ketenagaan juga belum siap karena latar belakang keilmuan tenaga kependidikan yang tidak linier. Sebaliknya, aspek kesiswaan telah siap mendukung madrasah mandiri, terbukti dengan keberhasilan siswa lolos SPBM masuk PTN ternama seperti UNAIR, UGM, ITB, dan UIN. Penelitian ini merekomendasikan penerapan MBS secara utuh, linearisasi keilmuan tenaga pendidik, serta penyediaan petunjuk teknis dari Departemen Agama untuk mendukung madrasah mandiri.